2020
DOI: 10.1002/ejhf.2027
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tafamidis doses in the Tafamidis in Transthyretin Cardiomyopathy Clinical Trial (ATTR‐ACT) and long‐term extension study

Abstract: Tafamidis is an effective treatment for transthyretin amyloid cardiomyopathy (ATTR-CM) in the Tafamidis in Transthyretin Cardiomyopathy Clinical Trial (ATTR-ACT). While ATTRACT was not designed for a dose-specific assessment, further analysis from ATTRACT and its long-term extension study (LTE) can guide determination of the optimal dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 26 publications
5
111
0
10
Order By: Relevance
“…4 Although the conclusions are reasonable, there are some issues deserving further considerations. During study extension, patients in the placebo arm of ATTR-ACT were randomized to tafamidis 80 mg or 20 mg. 4 Therefore, patients were not continuously on 80 mg or 20 mg for the entire study duration (ATTR-ACT plus extension study), with a poorly predictable impact on the observed relative efficacy of the two doses. 22 Another aspect not clarified by the study is whether the 80 mg dose can anticipate the moment where survival curves begin to diverge, which in ATTR-ACT was around 18 months from the start of treatment.…”
Section: The Optimal Dose For Patients With Cardiomyopathymentioning
confidence: 93%
See 3 more Smart Citations
“…4 Although the conclusions are reasonable, there are some issues deserving further considerations. During study extension, patients in the placebo arm of ATTR-ACT were randomized to tafamidis 80 mg or 20 mg. 4 Therefore, patients were not continuously on 80 mg or 20 mg for the entire study duration (ATTR-ACT plus extension study), with a poorly predictable impact on the observed relative efficacy of the two doses. 22 Another aspect not clarified by the study is whether the 80 mg dose can anticipate the moment where survival curves begin to diverge, which in ATTR-ACT was around 18 months from the start of treatment.…”
Section: The Optimal Dose For Patients With Cardiomyopathymentioning
confidence: 93%
“…22 Another aspect not clarified by the study is whether the 80 mg dose can anticipate the moment where survival curves begin to diverge, which in ATTR-ACT was around 18 months from the start of treatment. 1 The 80 mg and 20 mg dose seemed equally effective in reducing the decline in functional capacity or quality of life over time, 4 but further evidence is needed to clarify this point. Finally, this study did not explore the difference in survival between patients in New York Heart Association class I-II vs. III and its interaction with tafamidis dose.…”
Section: The Optimal Dose For Patients With Cardiomyopathymentioning
confidence: 99%
See 2 more Smart Citations
“…9 In an analysis of the long-term extension of ATTR-ACT, both tafamidis 80 mg and 20 mg reduced all-cause mortality and cardiovascular hospitalizations at 30 months compared with placebo, with the higher dose associated with better outcomes without safety issues in the long-term extension. 10 .…”
Section: Therapymentioning
confidence: 99%